Aqueous dispersion and method for producing laminate

JP7635620B2Active Publication Date: 2025-02-26AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021068538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-14
Publication Date
2025-02-26
Estimated Expiration
2041-04-14

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、分散安定性に優れる、テトラフルオロエチレン系ポリマーの粒子を含む分散液、及びかかる分散液から形成されるポリマー層を有する積層体を提供できる。本発明の分散液からは、低誘電正接等の電気特性、耐屈曲性等の柔軟性、金属箔等の基材との接着性·密着性、低線膨張性に優れる成形物、特に厚く平滑なポリマー層を形成できる。したがって、本発明の分散液から形成されるポリマー層を有する積層体は、例えばプリント基板の構成材料として有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635620000001
    Figure 0007635620000001
  • Figure 0007635620000002
    Figure 0007635620000002
Patent Text Reader

Abstract

To provide a dispersion liquid containing tetrafluoroethylene-based polymer particles excellent in dispersion stability, capable of obtaining a molding having excellent electrical characteristics, plasticity such as flex resistance, tackiness and adhesiveness to a substrate such as a metal foil and low linear expansion properties, and capable of forming a thick and smooth polymer layer.SOLUTION: An aqueous dispersion liquid includes tetrafluoroethylene-based polymer particles, inorganic particles with an average particle diameter smaller than 10 μm, polyalcohol and water. A mass ratio of the polyalcohol is 0.2 or more with regard to the water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion containing particles of a tetrafluoroethylene-based polymer, specific inorganic particles, and a specific ratio of polyhydric alcohols, and a method for producing a laminate having a polymer layer formed from such an aqueous dispersion. [Background technology]

[0002] Tetrafluoroethylene polymers such as polytetrafluoroethylene (PTFE) are excellent in physical properties such as electrical properties, water and oil repellency, chemical resistance, and heat resistance, and are used in various industrial applications. Dispersions containing particles of tetrafluoroethylene polymers are known as coating agents used to impart the above physical properties to the surface of a substrate, and such dispersions have also attracted attention as materials for forming dielectric layers of printed circuit boards compatible with high-frequency band frequencies.

[0003] On the other hand, in an attempt to improve the physical properties of such dispersions, Patent Documents 1 and 2 describe aqueous dispersions containing particles of a tetrafluoroethylene-based polymer to which a specific polyhydric alcohol, depolymerizable acrylic resin particles, and a nonionic surfactant have been added. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2003 / 011991 [Patent Document 2] International Publication No. 2021 / 045228 Summary of the Invention [Problem to be solved by the invention]

[0005] Aqueous dispersions containing particles of tetrafluoroethylene-based polymers, which generally have low surface tension, tend to have poor dispersion conditions, and therefore tend to cause coarse packing of the particles when the particles are applied to a substrate and baked to form a polymer layer. As a result, problems with the density of the polymer layer tend to occur, particularly when attempting to form a thick polymer layer. Specifically, when the polymer layer is formed on the surface of a substrate such as a metal foil by a continuous production process such as roll-to-roll, cracks and pinholes are likely to occur in the polymer layer. In addition, due to the low linear expansion of the tetrafluoroethylene-based polymer, the laminate consisting of the polymer layer and the substrate is likely to warp. When inorganic particles are blended into the aqueous dispersion to adjust the linear expansion coefficient of the formed molded product, the dispersibility and handling of the dispersion are reduced, and the particles and inorganic particles are likely to fall off (powder off) during coating. Also, the adhesion of the formed molded product to the substrate is likely to be reduced. The present inventors have found that this tendency becomes more pronounced when inorganic particles having a small particle size are blended into the dispersion liquid in order to improve the electrical properties of the polymer layer, such as the dielectric constant and the dielectric loss tangent.

[0006] As a result of intensive research, the present inventors have found that an aqueous dispersion containing tetrafluoroethylene polymer particles and inorganic particles of a specific particle size and having a specific ratio of polyhydric alcohol to water has excellent dispersion stability. They have also found that a thick and smooth molded product can be formed from such a dispersion, and that the molded product obtained is dense, has excellent electrical properties such as low dielectric tangent, flexibility such as bending resistance, and low linear expansion, and also has improved adhesion and adhesion to a substrate such as a metal foil. An object of the present invention is to provide a dispersion containing particles of a tetrafluoroethylene-based polymer which is excellent in dispersion stability, and which is capable of forming a thick and smooth polymer layer in the obtained molded product which has excellent electrical properties, flexibility such as bending resistance, low linear expansion properties, and adhesiveness and adhesion to substrates such as metal foils, and a method for producing a laminate having a polymer layer formed from such a dispersion. [Means for solving the problem]

[0007] The present invention has the following aspects. <1> An aqueous dispersion comprising tetrafluoroethylene polymer particles, inorganic particles having an average particle size of less than 10 μm, a polyhydric alcohol, and water, the mass ratio of the polyhydric alcohol to the water being 0.2 or more. <2> The tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having a carbonyl group-containing group or a hydroxyl group-containing group. <1> Aqueous dispersion of. <3> The tetrafluoroethylene-based polymer particles are particles of a heat-fusible tetrafluoroethylene-based polymer and particles of a non-heat-fusible tetrafluoroethylene-based polymer. <1> or <2> Aqueous dispersion of. <4> The inorganic particles are silica particles. <1> ~ <3> An aqueous dispersion of any one of the above. <5> The inorganic particles have a scale-like or substantially spherical shape. <1> ~ <4> An aqueous dispersion of any one of the above. <6> The content of the inorganic particles is greater than the content of the tetrafluoroethylene-based polymer. <1> ~ <5> An aqueous dispersion of any one of the above. <7> pH is in the range of 5 to 10; <1> ~ <6> An aqueous dispersion of any one of the above. <8> The polyhydric alcohol is an aliphatic polyhydric alcohol having a boiling point of 100°C or higher. <1> ~ <7> An aqueous dispersion of any one of the above. <9> Further containing aromatic resins <1> ~ <8> An aqueous dispersion of any one of the above. <10> The aromatic resin is a precursor of a water-soluble aromatic polyamideimide or a precursor of a water-soluble aromatic polyimide. <9> Aqueous dispersion of. <11> The content of the aromatic resin is less than 10% by mass based on the particles of the tetrafluoroethylene-based polymer. <9> or <10> Aqueous dispersion of. <12> Further comprising a surfactant, <1> ~ <11> An aqueous dispersion of any one of the above. <13> <1> ~ <12> a method for producing a laminate, comprising: applying any one of the aqueous dispersions in the above paragraphs to a surface of a substrate and heating the applied aqueous dispersion to form a polymer layer containing the tetrafluoroethylene-based polymer and the inorganic particles, thereby obtaining a laminate having the substrate and the polymer layer in this order. <14> The ten-point average roughness of the surface of the substrate is less than 0.1 μm; <13> Manufacturing method. <15> The thickness of the polymer layer is 25 μm or more. <13> or <14> Manufacturing method. Effect of the Invention

[0008] According to the present invention, it is possible to provide a dispersion containing tetrafluoroethylene-based polymer particles having excellent dispersion stability, and a laminate having a polymer layer formed from such a dispersion. From the dispersion of the present invention, a molded product having excellent electrical properties such as low dielectric tangent, flexibility such as bending resistance, adhesiveness and adhesion to a substrate such as a metal foil, and low linear expansion, particularly a thick and smooth polymer layer, can be formed. Therefore, the laminate having a polymer layer formed from the dispersion of the present invention is useful as a constituent material for, for example, a printed circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following terms have the following meanings. "Average particle size (D50)" is the cumulative 50% volumetric diameter of a target object (particle) determined by laser diffraction / scattering. In other words, particle size distribution is measured by laser diffraction / scattering, and a cumulative curve is calculated with the total volume of the particle group as 100%, and the average particle size (D50) is the particle size at the point on the cumulative curve where the cumulative volume is 50%. The D50 of a target object is determined by dispersing the particles in water and analyzing them by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "viscosity of the dispersion liquid" is the viscosity measured using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement was repeated three times, and the average value of the three measurements was used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."

[0010] The aqueous dispersion of the present invention (hereinafter also referred to as "the present dispersion") contains particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), inorganic particles having an average particle size of less than 10 μm, a polyhydric alcohol, and water, and the mass ratio of the polyhydric alcohol to water is 0.2 to 0.5.

[0011] This dispersion has excellent dispersion stability. In addition, the molded product (fired product) formed from this dispersion has excellent physical properties based on the F polymer, such as electrical properties, and physical properties based on the inorganic particles, such as linear expansion properties, and has excellent surface smoothness, flexibility, such as bending resistance, and adhesiveness and adhesion to the substrate. The reason why the dispersion stability of the present dispersion is improved is not necessarily clear, but is presumed to be, for example, as follows. Since F particles, which are particles of an F polymer having generally low surface energy, do not easily interact with inorganic particles, it can be considered that the F particles and inorganic particles are each in a state in which they are easily aggregated in the dispersion. In the present dispersion, it is considered that the polyhydric alcohol acts as a dispersant for the F particles and inorganic particles in the present dispersion, suppressing their aggregation. It is also considered that the polyhydric alcohol also acts as a rheology adjuster for the present dispersion, improving the dispersion stability and coatability of the present dispersion. Furthermore, it is considered that adjusting the content of the polyhydric alcohol relative to water to a predetermined range highly balances the action of suppressing the aggregation of the F particles and inorganic particles and the action of improving the rheology, thereby improving the dispersion stability and coatability of the present dispersion. It is also considered that the small particle size of the inorganic particles and the large surface area of ​​the inorganic particles improve the wettability of the inorganic particles and the polyhydric alcohol, enhancing these actions. Therefore, when this dispersion is applied and the F polymer is baked to form a molded product (polymer layer), the F particles and inorganic particles are highly packed together during application without falling off, and the polyhydric alcohol is highly removed during baking, so that a molded product with advanced physical properties is formed. As a result, it is believed that this dispersion has excellent dispersion stability, and that it is possible to easily form molded products from this dispersion that have excellent electrical properties, bending resistance, adhesion to substrates, low linear expansion, smoothness, etc., and are less prone to powder falling, and that have a high degree of both the physical properties of the F polymer and the physical properties of inorganic particles.

[0012] The F polymer in this dispersion is a polymer containing units (TFE units) based on tetrafluoroethylene (TFE). The F polymer may be heat-fusible or non-heat-fusible, but is preferably heat-fusible. The F polymer may be used alone or in combination of two or more types, and in this case, it is preferable that at least one of the F polymers is heat-fusible. In this case, a molded product formed from the dispersion liquid is likely to have excellent flexibility and adhesiveness / cohesion to a substrate. Note that the term "thermal melt property" refers to a polymer having melt fluidity at which the melt flow rate is 1 to 1000 g / 10 min at a temperature 20° C. or more higher than the melting temperature of the polymer under a load of 49 N. When the F polymer is heat-meltable, the melting temperature is preferably 200° C. or higher, more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. In such a case, a molded product formed from the present dispersion tends to have excellent heat resistance.

[0013] The fluorine atom content in the F polymer is preferably 70% by mass or more, more preferably 70 to 76% by mass. Due to the above-mentioned mechanism of action, the present dispersion liquid is particularly likely to improve the water dispersibility of the particles of the F polymer having a high fluorine atom content. The glass transition point of the F polymer is preferably from 75 to 125°C, more preferably from 80 to 100°C.

[0014] Examples of F polymers include polytetrafluoroethylene (PTFE), polymers containing TFE units and units based on ethylene (ETFE), polymers containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), and polymers containing TFE units and units based on hexafluoropropene (HFP) (FEP). Each of ETFE, PFA, and FEP may further contain other units. As PAVE, CF2=CFOCF3, CF2=CFOCF2CF3, and CF2=CFOCF2CF2CF3 (PPVE) are preferred, and PPVE is more preferred. The F polymer is preferably PFA or FEP, more preferably PFA.

[0015] At least one of the F polymers preferably has an oxygen-containing polar group, which improves the affinity of the F polymer with the inorganic particles and the polyhydric alcohol, and therefore the dispersion tends to have excellent dispersion stability. The oxygen-containing polar group may be contained in a unit in the F polymer, or may be contained in a terminal group of the main chain of the F polymer. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having an oxygen-containing polar group obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The oxygen-containing polar group is preferably a hydroxyl group-containing group, a carbonyl group-containing group, or a phosphono group-containing group, and from the viewpoint of the dispersion stability of the present dispersion, a hydroxyl group-containing group and a carbonyl group-containing group are more preferable, and a carbonyl group-containing group is even more preferable.

[0016] The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, and more preferably -CF2CH2OH, -C(CF3)2OH, or a 1,2-glycol group (-CH(OH)CH2OH). The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)- etc.) or a carbonate group (-OC(O)O-), more preferably an acid anhydride residue. When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000, and further preferably 800 to 1500. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133. Moreover, the monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH").

[0017] The F polymer is preferably a polymer having a carbonyl group-containing group or a hydroxyl group-containing group, including a TFE unit and a PAVE unit, more preferably a polymer containing a TFE unit, a PAVE unit, and a unit based on a monomer having a carbonyl group-containing group or a hydroxyl group-containing group, and even more preferably a polymer containing these units in the amounts, in this order, of 90 to 99 mol %, 0.5 to 9.97 mol %, and 0.01 to 3 mol %, based on the total units. Specific examples of such polymers include those described in WO 2018 / 16644. These F polymers not only have excellent dispersion stability, but also tend to be distributed more densely and uniformly in the molded product (polymer layer, etc.) obtained from the dispersion. Furthermore, they tend to form microspherulites in the molded product, which tends to increase adhesion with other components. As a result, molded products with excellent physical properties such as electrical properties are more likely to be obtained.

[0018] In the present dispersion, the D50 of the F particles is preferably 0.1 to 25 μm. The D50 of the F particles is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 8 μm or less. The D50 of the F particles is preferably 0.2 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. With a D50 in this range, the fluidity and dispersibility of the F particles tend to be good.

[0019] From the viewpoint of dispersion stability of this dispersion, the bulk density of F particles is 0.15 g / m 2 More than 0.20 g / m is preferable. 2 More preferably, the bulk density of the F particles is 0.50 g / m 2 Less than 0.35 g / m is preferred. 2 The following is more preferred: The specific surface area of ​​F particles is 1 to 8 m 2 / g is preferable, and 1 to 3m 2 / g is more preferred.

[0020] One type of F particles may be used, or two or more types may be used. When two types of F particles are used, the F particles preferably include particles of a non-thermofusible F polymer (preferably PTFE) and particles of an F polymer (preferably a polymer having a carbonyl group-containing group or a hydroxyl group-containing group, including the above-mentioned TFE unit and PAVE unit) having a melting temperature of 200 to 320°C. It is more preferable that the content by mass of the former particles is greater than the content by mass of the latter particles. In this case, the proportion of the latter particles in the total of the former particles and the latter particles is preferably 25% by mass or less, more preferably 15% by mass or less, and in this case, the proportion is preferably 0.1% by mass or more, more preferably 1% by mass or more. The present dispersion is likely to have excellent dispersion stability, ease of handling, and long-term storage stability. In addition, during preparation of the present dispersion or during formation of a molded product, PTFE is appropriately fibrillated, which makes it easier for the inorganic particles to be supported in the molded product, and makes it easier to form a molded product based on PTFE that has excellent physical properties and high strength. In this case, preferred embodiments are those in which the particles of the non-thermofusible F polymer have a D50 of 0.1 to 1 μm and the particles of the F polymer having a melting temperature of 200 to 320° C. have a D50 of 0.1 to 1 μm, and those in which the particles of the non-thermofusible F polymer have a D50 of 0.1 to 1 μm and the particles of the F polymer having a melting temperature of 200 to 320° C. have a D50 of 1 to 4 μm.

[0021] The F particles may contain resins or inorganic substances other than the F polymer, but preferably contain the F polymer as the main component. The content of the F polymer in the F particles is preferably 80% by mass or more, more preferably 100% by mass. Examples of the resin include heat-resistant resins such as aromatic polyester, polyamideimide, (thermoplastic) polyimide, polyphenylene ether, polyphenylene oxide, and maleimide. Examples of the inorganic material include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, and the like), boron nitride, and magnesium metasilicate (steatite). At least a part of the surface of the inorganic material may be surface-treated. F particles containing a resin or inorganic substance other than an F polymer may have a core-shell structure having an F polymer as a core and a resin or inorganic substance other than an F polymer as a shell, or may have a core-shell structure having an F polymer as a shell and a resin or inorganic substance other than an F polymer as a core. Such F particles are obtained, for example, by bonding (collision, aggregation, etc.) particles of an F polymer and a resin or inorganic substance other than an F polymer.

[0022] The content of F particles in the present dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total mass of the present dispersion. The content of F particles is preferably 40% by mass or less, more preferably 20% by mass or less, based on the total mass of the present dispersion.

[0023] The inorganic particles contained in the present dispersion are preferably nitride particles or inorganic oxide particles, more preferably boron nitride particles, beryllium oxide particles, silicate particles (silica particles, wollastonite particles, talc particles), metal oxide particles (cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.) particles or magnesium metasilicate (steatite) particles, and even more preferably silica particles. These inorganic particles may be fired ceramic particles. The inorganic particles may be used alone or in combination of two or more kinds. When two or more kinds of inorganic particles are used in combination, two kinds of silica particles may be used in combination, or silica particles and other inorganic particles may be used in combination. By containing inorganic particles in the dispersion, the molded product produced from the dispersion is likely to have excellent electrical properties and low linear expansion. In addition, even if the dispersion contains inorganic particles, the dispersion is excellent in dispersion stability due to the above-mentioned mechanism of action, and it is easy to obtain a dense molded product. Therefore, it is easy to form a molded product from the dispersion that has high physical properties of the F polymer and the inorganic particles.

[0024] At least a part of the surface of the inorganic particles is preferably surface-treated with a silane coupling agent (3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, etc.). Such inorganic particles have excellent affinity with the F particles and are likely to improve the dispersibility of the present dispersion.

[0025] The inorganic particles contained in the dispersion have an average particle size (D50) of less than 10 μm. The inorganic particles preferably have a D50 of more than 0.1 μm and less than 10 μm. D50 is more preferably 8 μm or less, and more preferably 5 μm or less. D50 is preferably 0.25 μm or more, and more preferably 0.5 μm or more. The specific surface area of ​​the inorganic particles is 1 to 20 m 2 / g is preferable, and 1 to 5m 2 / g is more preferred.

[0026] The shape of the inorganic particles may be any of granular, needle-like (fibrous), and plate-like. Specific shapes of the inorganic particles include spherical, scale-like, layered, leaf-like, apricot-like, columnar, cockscomb-like, equiaxial, leaf-like, mica-like, block-like, flat, wedge-like, rosette-like, mesh-like, and prismatic. The shape of the inorganic particles is preferably substantially spherical or scale-like, more preferably substantially spherical with D50 of more than 0.1 μm and less than 10 μm and substantially free of particles with a particle diameter of 3 μm or more, or scale-like with an average major axis of 1 μm or more and an aspect ratio of 5 or more, and even more preferably substantially spherical. The term "approximately spherical inorganic particles" refers to inorganic particles in which, when observed with a scanning electron microscope (SEM), the proportion of spherical particles having a ratio of minor axis to major axis of 0.7 or more is 95% or more. In this case, the inorganic particles become more easily wetted in the dispersion, and the interaction with the F particles is easily enhanced. In addition, in a molded product formed from the dispersion, the inorganic particles and the F polymer are more easily distributed uniformly, and the physical properties of both are easily expressed in a well-balanced manner.

[0027] Specific examples of suitable inorganic particles include silica particles (such as the "Admafine (registered trademark)" series manufactured by Admatechs Co., Ltd.), zinc oxide surface-treated with an ester such as propylene glycol dicaprate (such as the "FINEX (registered trademark)" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica (such as the "SFP (registered trademark)" series manufactured by Denka Co., Ltd.), titanium oxide coated with polyhydric alcohol and inorganic substances (such as the "Tipaque (registered trademark)" series manufactured by Ishihara Sangyo Kaisha, Ltd.), and rutile-type titanium oxide surface-treated with alkylsilane (such as the "Taika Co., Ltd. "JMT (registered trademark)" series, etc.), hollow silica particles ("E-SPHERES" series manufactured by Taiheiyo Cement Corporation, "Silinax" series manufactured by Nippon Steel Mining Co., Ltd., "Ecocospher" series manufactured by Emerson & Cumming Co., Ltd., etc.), talc particles ("SG" series manufactured by Nippon Talc Co., Ltd., etc.), steatite particles ("BST" series manufactured by Nippon Talc Co., Ltd., etc.), boron nitride particles ("UHP" series manufactured by Showa Denko KK, "Denka Boron Nitride" series ("GP", "HGP" grades), etc.) manufactured by Denka Co., Ltd.

[0028] In the present dispersion, the content of inorganic particles is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the present dispersion, and preferably 70% by mass or less, more preferably 50% by mass or less. In the present dispersion, the content of inorganic particles is preferably greater than the content of F polymer. Specifically, the ratio of the mass content of inorganic particles to the mass content of F particles in the present dispersion is greater than 1, more preferably 1.25 or more, and even more preferably 1.5 or more. The ratio is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less. When it is in this range, it becomes possible to easily form a thick molded product from the present dispersion without defects such as powder falling while maintaining the dispersion stability of the F particles and inorganic particles, and the physical properties of the obtained molded product are likely to be improved.

[0029] The total content of the F particles and inorganic particles in the present dispersion is preferably 20% by mass or more based on the total mass of the present dispersion. The total content is more preferably 30% by mass or more, and even more preferably 40% by mass or more. The total content is preferably 70% by mass or less. In this case, a molded product such as a coating film can be formed from the dispersion liquid with a high thickness and high uniformity, and the physical properties due to the F polymer and the physical properties due to the inorganic particles are easily expressed to a high degree. That is, even when the content of the F particles and the inorganic particles is in such a high range, the dispersion liquid has excellent dispersion stability due to the above-mentioned mechanism of action, and the physical properties of the molded product can be improved.

[0030] The polyhydric alcohol contained in the present dispersion is a compound having two or more alcoholic hydroxyl groups. The polyhydric alcohol is preferably an aliphatic polyhydric alcohol having two or three alcoholic hydroxyl groups, no nitrogen atom, and a boiling point of 100° C. or higher. The boiling point of the polyhydric alcohol is preferably 150° C. or higher, more preferably 200° C. or higher, and more preferably 340° C. or lower. Moreover, the polyhydric alcohol is preferably one that is miscible with water.

[0031] Examples of polyhydric alcohols include ethylene glycol (198°C), 1,2-propanediol (188°C), 1,3-propanediol (214°C), 1,2-butanediol (190°C), 1,3-butanediol (208°C), 1,4-butanediol (229°C), 1,5-pentanediol (242°C), 2-butene-1,4-diol (235°C), glycerin (290°C), 2-ethyl-2-hydroxymethyl-1,3-propanediol (295°C), and 1,2,6-hexanetriol (178°C / 666 Pa). The boiling points of the polyhydric alcohols are shown in parentheses. The polyhydric alcohol is preferably glycerin, which improves the dispersibility of the F particles and inorganic particles in the dispersion, and improves the electrical properties, bending resistance, adhesion to the substrate, and low linear expansion of the resulting molded product, and is less likely to fall off. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0032] In the present dispersion, the content mass ratio of the polyhydric alcohol to water is 0.2 or more. Such a content mass ratio is more preferably 0.25 or more, and even more preferably 0.5 or more. Such a content mass ratio is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less. When the content mass ratio is within this range, the aggregation suppression effect and rheology adjustment effect of the polyhydric alcohol are exhibited in a well-balanced manner, and the present dispersion tends to have excellent dispersion stability.

[0033] The water content in the present dispersion is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the present dispersion, and is preferably 60% by mass or less, more preferably 50% by mass or less. The content of the polyhydric alcohol in the present dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total mass of the present dispersion, and is preferably 70% by mass or less, more preferably 60% by mass or less. Within this range, the dispersion can be handled as a liquid or paste, and its dispersion stability and coatability are more likely to be improved.

[0034] In addition to water and the polyhydric alcohol, the dispersion may further contain a compound as a liquid dispersion medium within a range that does not impair the effects of the present invention. Such a compound is preferably liquid at 25°C under atmospheric pressure and miscible with water. The boiling point of such a compound is preferably in the range of 50 to 240°C, and specific examples include methanol, ethanol, isopropanol, acetone, methyl ethyl ketone, N-methyl-2-pyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0035] The present dispersion may further contain an aromatic resin. The aromatic resin may be thermoplastic or thermosetting. The aromatic resin may be contained in the present dispersion as a precursor thereof. The aromatic resin may be dissolved in the present dispersion or may be dispersed without being dissolved. The aromatic resin is preferably water-soluble.

[0036] Examples of the aromatic resin include aromatic epoxy resins, phenolic resins, aromatic polyester resins (such as liquid crystalline aromatic polyesters), aromatic polyesteramides (such as liquid crystalline aromatic polyesteramides), aromatic maleimides, polyphenylene ethers, aromatic polyimides, aromatic polyimide precursors (polyamic acids or salts thereof), aromatic polyamideimides, aromatic polyamideimide precursors, aromatic polyetherimides, and aromatic polyetherimide precursors. Of these, aromatic polyimide precursors, aromatic polyamideimides, or aromatic polyamideimide precursors are preferred, and water-soluble aromatic polyamideimide precursors or water-soluble aromatic polyimide precursors are more preferred. In this case, the aromatic resin easily interacts with the F polymer, and furthermore, a molded article formed from this dispersion tends to have excellent adhesion to a substrate such as a metal foil and excellent UV absorption properties.

[0037] Examples of aromatic polyimide precursors include polyamic acid obtained by polymerizing tetracarboxylic dianhydride and diamine in a solvent, and polyamic acid salts obtained by reacting the polyamic acid with aqueous ammonia or organic amine. An aqueous solution of polyamic acid can be prepared by dissolving the polyamic acid salt in water. Specific examples of aromatic polyimide resins or their precursors include the "Neoprim (registered trademark)" series (manufactured by Mitsubishi Gas Chemical Company, Inc.), the "Spixeria (registered trademark)" series (manufactured by Somar), the "Q-PILON (registered trademark)" series (manufactured by PI Technology Research Institute), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "Tomide (registered trademark)" series (manufactured by T&K TOKA Corporation), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and the "Upia (registered trademark)-AT" series (manufactured by Ube Industries, Ltd.).

[0038] Examples of aromatic polyamideimide resins or precursors thereof include polyamideimide resins or precursors thereof obtained by reacting diisocyanate and / or diamine with tribasic acid anhydride (or tribasic acid chloride) as an acid component. Specific examples of aromatic polyamideimide resins or precursors thereof include "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.).

[0039] When the present dispersion further contains an aromatic resin, the content thereof is preferably 0.01% by mass or more, more preferably 1% by mass or more, based on the total mass of the present dispersion, and the content of the aromatic resin is preferably 5% by mass or less, more preferably 3% by mass or less. The content of the aromatic resin in the dispersion is preferably less than 10% by mass, more preferably 5% by mass or less, relative to the F particles in the dispersion, and is preferably 0.1% by mass or more relative to the F particles. If the content of the aromatic resin is in such a low range, the dispersion stability of the F particles is improved, and the physical properties of the molded product obtained from this dispersion tend to be improved. Although the reason for this is not necessarily clear, it is thought that the aromatic resin functions highly as a dispersant and binder for the low hydrophilic F particles, that is, it adheres to the surface of the F particles and promotes dense sintering of the F particles when forming the molded product.

[0040] The present dispersion may further contain a surfactant from the viewpoint of improving the dispersibility of the F particles and the inorganic particles. The surfactant is preferably nonionic. The surfactant is preferably a glycol surfactant, an acetylene surfactant, a silicone surfactant or a fluorine-based surfactant, and more preferably a silicone surfactant. The surfactant may be used alone or in combination of two or more. When two types of nonionic surfactants are used, the nonionic surfactants are preferably a silicone-based surfactant and a glycol-based surfactant.

[0041] Specific examples of surfactants include the "Ftergent" series (manufactured by Neos Co., Ltd., Ftergent is a registered trademark), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd., Surflon is a registered trademark), the "Megafac" series (manufactured by DIC Corporation, Megafac is a registered trademark), the "Unidyne" series (manufactured by Daikin Industries, Ltd., Unidyne is a registered trademark), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan Co., Ltd.), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), and the "Tergitol" series (manufactured by The Dow Chemical Company, "Tergitol TMN-100X", etc.).

[0042] The present dispersion may further contain a resin material other than the F polymer and the aromatic resin described above, from the viewpoint of improving the adhesiveness and low linear expansion of the molded product formed from the present dispersion. Such a resin material may be thermosetting or thermoplastic, may be modified, and may be dissolved in the present dispersion or may be dispersed without being dissolved. Examples of such resin materials include non-aromatic maleimide resins, urethane resins, polyimide resins, polyamic acids, polyamideimides, and polyvinyl acetal resins. When the present dispersion further contains a resin material, the content thereof is preferably 40% by mass or less based on the total mass of the present dispersion.

[0043] The pH of the present dispersion is preferably in the range of 5 to 10, and more preferably in the range of 7 to 9. In this case, the present dispersion tends to have excellent dispersion stability and storage stability. The dispersion may further comprise a pH adjuster or buffer. pH adjusters include amines, ammonia, and citric acid. Examples of pH buffers include tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium hydrogen carbonate, ammonium carbonate, and ammonium acetate. When the present dispersion further contains a pH adjuster or a pH buffer, these may be added to water before the preparation of the present dispersion, or may be added at any stage of the preparation of the present dispersion.

[0044] In addition to the above-mentioned components, the present dispersion may further contain other components such as a thixotropy imparting agent, a viscosity adjusting agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a flame retardant, and various fillers, as long as the effects of the present invention are not impaired.

[0045] The viscosity of the dispersion is preferably 10 mPa·s or more, more preferably 30 mPa·s or more, and even more preferably 50 mPa·s or more. The viscosity of the dispersion is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less, and even more preferably 1,000 mPa·s or less.

[0046] The thixotropy ratio of the present dispersion is preferably 1.0 or more. The thixotropy ratio of the present dispersion is preferably 3.0 or less, more preferably 2.0 or less. In this case, the present dispersion has excellent coatability and homogeneity, and is likely to form a denser molded product (polymer layer, etc.).

[0047] In this dispersion, the dispersion layer ratio is preferably 60% or more, more preferably 70% or more, and more preferably 80% or more. Here, the dispersion layer ratio is a value calculated by the following formula from the height of the entire dispersion in the screw tube and the height of the sedimentation layer (dispersion layer) before and after standing when the dispersion (18 mL) is placed in a screw tube (internal volume: 30 mL) and left at rest at 25° C. for 14 days. Note that if no sedimentation layer is confirmed after standing and there is no change in the state, the dispersion layer ratio is considered to be 100%, assuming that there is no change in the height of the entire dispersion. Dispersion layer rate (%) = (height of sedimentation layer) / (total height of dispersion liquid) x 100

[0048] Due to the above-mentioned mechanism of action, the present dispersion has excellent dispersion stability, particularly long-term storage stability. When the present dispersion is allowed to stand at 25° C. for 30 days, the fluctuation range (absolute value) of the thixotropy ratio of the present dispersion is preferably 3 or less, and more preferably less than 1.

[0049] This dispersion can be prepared by mixing F particles, inorganic particles, polyhydric alcohol, and water. Examples of the mixing method include a method of adding each component all at once or sequentially and mixing; a method of mixing F particles and inorganic particles to prepare a powder composition, and then adding polyhydric alcohol and water and mixing; a method of previously mixing F particles and water or polyhydric alcohol, and inorganic particles and water or polyhydric alcohol, respectively, and then further mixing the obtained two mixtures. In addition, when the present dispersion liquid further contains a surfactant, an aromatic resin, or other resin materials, it is preferable to add them simultaneously when dispersing the F particles, inorganic particles, and polyhydric alcohol in water in advance, or to add them to the water in advance before dispersing the F particles and inorganic particles. When the present dispersion liquid contains an aromatic resin, it may be mixed with the F particles as a varnish of the aromatic resin. Examples of the solvent constituting the varnish include N-methyl-2-pyrrolidone, cyclohexanone, and toluene. When the F particles contain two types of F particles, a mixture containing the second F particles and water may be added to a mixture containing the first F particles, inorganic particles, polyhydric alcohol, and water.

[0050] Examples of mixing methods for preparing the present dispersion include stirring using a stirring device equipped with uniaxial or multiaxial blades (stirring impellers) such as a propeller blade, turbine blade, paddle blade, or shell-shaped blade, or a Henschel mixer, pressure kneader, Banbury mixer, or planetary mixer; mixing using a disperser that uses media such as a ball mill, attritor, basket mill, sand mill, sand grinder, Dyno Mill (a bead mill using grinding media such as glass beads or zirconium oxide beads), Dispermat, SC mill, spike mill, or agitator mill; and mixing using a disperser that does not use media, such as a high-pressure homogenizer such as a Microfluidizer, Nanomizer, or Ultimizer, an ultrasonic homogenizer, a Dissolver, a Disper, or a high-speed impeller disperser.

[0051] Among them, the device used for mixing is preferably a Henschel mixer, a pressure kneader, a Banbury mixer or a planetary mixer, and more preferably a planetary mixer. The planetary mixer has two agitating blades that rotate and revolve around each other, and is structured to agitate and knead the kneaded material in the agitation tank. Therefore, there is little dead space in the agitation tank where the agitating blades do not reach, and the load on the blades is reduced, allowing the composition to be kneaded to a high degree. In other words, the F particles can be kneaded while being wetted with a liquid dispersion medium while suppressing aggregation of the F particles, while allowing the F particles, inorganic particles, and polyhydric alcohol to interact with each other to a high degree, and when the kneaded material is further mixed with a liquid dispersion medium, the present dispersion liquid with excellent dispersion stability is easily obtained. In addition, the component concentrations of the present dispersion liquid can be easily adjusted, and a thick molded product (polymer layer, etc.) with excellent surface smoothness and uniformity can be easily formed from the present dispersion liquid.

[0052] The present dispersion may be prepared by mixing a composition containing F particles and a polyhydric alcohol or water to obtain a mixture, and then further adding a polyhydric alcohol or water to the mixture to adjust the viscosity. In this case, the inorganic particles may be added to the composition before mixing, or may be added when the mixture is mixed with the polyhydric alcohol or water.

[0053] This dispersion can be used in applications such as forming insulating layers for printed wiring boards, bonding ceramic parts or metal parts together in vehicle engines, imparting corrosion resistance to heat exchangers and the fins or tubes that constitute them, impregnating and drying coils used in thermal interface materials, power module substrates, and motors and other power devices to form thermally conductive, heat-resistant coating layers, and coating the inside and outside of glass containers such as medical vials and syringes.

[0054] This dispersion has excellent dispersion stability and long-term storage stability, and can be used to form molded products that have excellent flexibility such as bending resistance, i.e., excellent crack resistance and low linear expansion, exhibit strong adhesion to substrates, and are resistant to powder falling. This dispersion is applied to at least one surface of a substrate to form a liquid coating, which is then heated to remove the dispersion medium to form a dry coating, and the dry coating is further heated to bake the F polymer, thereby obtaining a laminate having a polymer layer (hereinafter also referred to as "F layer") on the surface of the substrate, which contains the F polymer and inorganic particles and preferably has a higher inorganic particle content than the F polymer content.

[0055] Examples of the substrate include metal substrates such as metal foils made of copper, nickel, aluminum, titanium, and alloys thereof, heat-resistant films made of heat-resistant resins such as tetrafluoroethylene polymers, polyimides, polyarylates, polysulfones, polyarylsulfones, polyamides, polyetheramides, polyphenylene sulfides, polyaryletherketones, polyamideimides, liquid crystal polyesters, and liquid crystal polyesteramides, and prepregs which are precursors of fiber-reinforced resin substrates. Among these, metal substrates are preferred, and copper foils are more preferred. The ten-point average roughness of the surface of the substrate is preferably less than 0.1 μm, more preferably 0.05 μm or less. The ten-point average roughness is preferably 0.001 μm or more. Even with such a non-roughened substrate, a laminate with excellent peel strength can be obtained from the present dispersion, and a printed circuit board or the like with excellent transmission characteristics can be formed from the laminate. The ten-point average roughness of the surface of the substrate is a value specified in Appendix JA of JIS B 0601:2013. The thickness of the substrate is preferably 2 to 100 μm. When the substrate is a metal foil, the thickness of the substrate is preferably 1 to 35 μm. The substrate may also be a metal foil with a carrier, which is an ultra-thin copper foil (thickness 2 to 5 μm) laminated on a carrier copper foil via a release layer.

[0056] The method for applying the present dispersion to the surface of a metal substrate (base material) may be any method that forms a stable liquid coating (wet film) of the present dispersion on the surface of the metal substrate, and includes coating, droplet ejection, and immersion methods, with the coating method being preferred. The coating method allows for efficient formation of a liquid coating on the surface of a metal substrate with simple equipment. Examples of the coating method include spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating.

[0057] When drying the liquid coating, the liquid coating is heated at a temperature at which the water and polyhydric alcohol volatilize, and a dry coating is formed on the surface of the metal substrate (base material). The heating temperature in such drying is preferably the boiling point of the polyhydric alcohol +50°C or less, more preferably the boiling point of the polyhydric alcohol or less, and even more preferably the boiling point of the polyhydric alcohol -50°C or less. The drying temperature is preferably 120°C to 200°C. Air may be blown in the process of removing the water and polyhydric alcohol. During drying, the water and polyhydric alcohol do not necessarily have to be completely evaporated, but may be evaporated to an extent that the layer shape after holding is stable and a free-standing film can be maintained.

[0058] When baking the F polymer, it is preferable to heat the dried coating to a temperature equal to or higher than the melting temperature of the F polymer, and the heating temperature is preferably 380° C. or lower, more preferably 350° C. or lower. Examples of the heating method include a method using an oven, a method using a ventilated drying furnace, and a method using heat rays such as infrared rays. Heating may be performed under either normal pressure or reduced pressure. The heating atmosphere may be any of an oxidizing gas atmosphere (oxygen gas, etc.), a reducing gas atmosphere (hydrogen gas, etc.), and an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.). The heating time is preferably from 0.1 to 30 minutes, more preferably from 0.5 to 20 minutes. By heating under the above conditions, the F layer can be suitably formed while maintaining high productivity.

[0059] The thickness of the F layer is preferably 0.1 to 200 μm, more preferably 25 μm or more, and more preferably 50 μm or more. In particular, the present dispersion can be suitably used for the purpose of forming a thick F layer of 25 μm or more by repeating the operation of applying it to the surface of a metal substrate and heating it several times. The F layer is formed through the steps of coating the modified dispersion, drying, and firing as described above. These steps may be carried out once or twice or more. From the viewpoint of obtaining a thick film having excellent smoothness, the steps of coating, drying and baking the present dispersion may be carried out multiple times. For example, the present dispersion is applied to a substrate, and the water and polyhydric alcohol are removed by heating to form a film. The present dispersion may be further applied onto the formed film to remove the water and polyhydric alcohol, and the F polymer may be further baked by heating to form an F layer.

[0060] The peel strength between the F layer and the base layer is preferably 10 N / cm or more, more preferably 15 N / cm or more. The above peel strength is preferably 100 N / cm or less. By using this dispersion, a laminate having such excellent peel strength can be easily formed without impairing the physical properties of the F polymer in the F layer.

[0061] The porosity of the F layer is preferably 30% or less, more preferably 20% or less. The porosity is preferably 0.1% or more, more preferably 1% or more. From this dispersion, it is easy to form an F layer with such a low porosity. The porosity is determined by determining the void portion of the F layer by image processing from an SEM photograph of the cross section of a molded product observed using a scanning electron microscope (SEM), and is the percentage (%) obtained by dividing the area occupied by the void portion by the area of ​​the F layer. The area occupied by the void portion is determined by approximating the void portion as a circle.

[0062] The dispersion may be applied to only one surface of the substrate, or may be applied to both surfaces of the substrate. In the former case, a laminate having a substrate layer made of the substrate and an F layer on one surface of the substrate layer is obtained, while in the latter case, a laminate having a substrate layer made of the substrate and an F layer on both surfaces of the substrate layer is obtained. The latter laminate is less likely to warp, and therefore has excellent handling properties during processing. Specific examples of such laminates include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and an F layer on both surfaces of the polyimide film. These laminates are suitable as printed circuit board materials, etc., because they have excellent physical properties such as electrical properties, and can be used in the manufacture of flexible printed circuit boards and rigid printed circuit boards.

[0063] The outermost surface of the substrate may be further subjected to a surface treatment in order to further improve its low linear expansion property and adhesiveness. Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment. The annealing conditions are preferably a temperature of 120 to 180° C., a pressure of 0.005 to 0.015 MPa, and a time of 30 to 120 minutes. Examples of gases used in the plasma treatment include oxygen gas, nitrogen gas, rare gas (argon, etc.), hydrogen gas, ammonia gas, and vinyl acetate. These gases may be used alone or in combination of two or more.

[0064] On the outermost surface of the laminate, another substrate may be further laminated. Other substrates include metal substrates, heat-resistant resin films, prepregs which are precursors of fiber-reinforced resin plates, laminates having a heat-resistant resin film layer, and laminates having a prepreg layer. The metal substrate may be any of the metal substrates described above. The heat-resistant resin film is a film containing one or more types of heat-resistant resin, and examples of the heat-resistant resin include the resins described above. As a method for lamination, a method of hot pressing the laminate and another substrate can be mentioned.

[0065] Laminates of the F layer and other substrates are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, paints, cosmetics, etc., and specifically, are useful as electric wire coating materials (aircraft electric wires, etc.), electrical insulating tapes, insulating tapes for oil drilling, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding members (load bearings, sliding shafts, valves, bearings, gears, cams, belt conveyors, food transport belts, etc.), tools (shovels, files, saws, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, and container coating materials.

[0066] The above describes the method for producing a laminate having the present dispersion and a polymer layer formed from the present dispersion, but the present invention is not limited to the configuration of the above-mentioned embodiment. For example, the present dispersion may have any other configuration added to the configuration of the above embodiment, or may be replaced with any configuration that exhibits a similar function. In addition, the method for producing a laminate having a polymer layer formed from the present dispersion may have any other process added to the configuration of the above embodiment, or may be replaced with any process that produces a similar effect. EXAMPLES

[0067] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Details of each ingredient [F particle] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles (D50: 2.1μm) made of polymer (melting temperature: 300℃) with 1000 particles per particle F Particle 2: Particles made of non-thermofusible PTFE (D50: 0.3 μm) [F dispersion] F dispersion 1: Aqueous dispersion containing 60% by mass of F particles 2 (AGC Corporation, product number AD-915E) [Inorganic particles] Inorganic particles 1: Nearly spherical silica particles (D50: 1.0 μm) Inorganic particles 2: Nearly spherical silica particles (D50: 10.2 μm) [Polyhydric alcohol] gly: glycerin [Surfactants] Surfactant 1: Nonionic surfactant (BYK Japan, "BYK-3450") [Aromatic resin varnish] Varnish 1: Water varnish containing a precursor of water-soluble aromatic polyamideimide (PAI1) ("HPC-1000" manufactured by Showa Denko Materials Co., Ltd.)

[0068] 2. Example of production of aqueous dispersion [Example 1-1] F particles 1, inorganic particles 1, varnish 1, surfactant 1, gly, ammonia water, and ammonium hydrogen carbonate were added to the pot, and zirconia balls were then added. The pot was then rolled at 150 rpm for 1 hour to prepare a liquid composition. The prepared liquid composition and F dispersion 1 were added to another pot, and zirconia balls were added. The pot was then rolled at 150 rpm for 1 hour to obtain an aqueous dispersion 1 (viscosity: 500 mPa s, pH: 8.0) containing F particles 1 (18 parts by mass), F particles 2 (20 parts by mass), inorganic particles 1 (60 parts by mass), PAI 1 (2 parts by mass), surfactant 1 (1 part by mass), gly (48 parts by mass), and water (12 parts by mass). The mass ratio of polyhydric alcohol to water in the aqueous dispersion 1 was 4.

[0069] [Example 1- 3 ]~[Example 1- 4 ] Except for changing the type and amount of inorganic particles, and the amounts of F particles 1, F particles 2, varnish 1, surfactant 1, gly, and water as shown in Table 1, the same procedure as in Example 1-1 was repeated to prepare an aqueous dispersion. 3 ~ 4 obtained.

[0070] [Table 1]

[0071] 3. Example of laminate manufacturing [Example 2-1] A wet film was formed on the surface of non-roughened copper foil (surface ten-point average roughness: 0.05 μm or less, thickness: 18 μm) by a roll-to-roll process using a small-diameter gravure reverse method. The copper foil on which the wet film was formed was then passed through a ventilated drying furnace (furnace temperature 120°C) to form a dry film, and further passed through a 380°C baking furnace in a nitrogen gas atmosphere to heat and bake F particles 1 and F particles 2. As a result, a laminate 1 was obtained, which had a copper foil and a polymer layer (thickness: 100 μm) formed on the surface of the copper foil from the aqueous dispersion liquid 1. [Example 2- 3 ]~[Example 2- 4 ] Aqueous dispersion 1 Aqueous dispersion 3 ~ 4 The laminate was manufactured in the same manner as in Example 2-1, except that the change was made to 3 ~ 4obtained.

[0072] 4. Evaluation 4-1. Dispersion stability of dispersion liquid Each dispersion (18 mL) was placed in a screw tube (internal volume: 30 mL) and left to stand for 14 days at 25° C. The dispersion layer ratio was calculated from the total height of the dispersion in the screw tube and the height of the sedimentation layer (dispersion layer) before and after standing using the following formula, and the dispersion stability was evaluated according to the following criteria. [Evaluation Criteria] ○: Dispersion layer rate is 60% or more ×: Dispersion layer rate is less than 60%

[0073] 4-2. Film-forming properties of dispersion liquid When a laminate was produced from each dispersion, the surface of the dried coating was visually observed, and the presence or absence of powder falling off was evaluated according to the following criteria to evaluate the film-forming properties. [Evaluation Criteria] 〇: No powder fall observed △: Powder fall is observed in some parts of the dried coating. ×: Powder fall is observed over the entire surface of the dried coating.

[0074] 4-3.Surface smoothness of laminate The surface smoothness of the polymer layer of each laminate was evaluated by measuring the thickness at the center and ends of the polymer layer in the short direction, calculating the ratio of the end thickness to the center thickness, and according to the following criteria. [Evaluation Criteria] ○: Thickness ratio is 1.07 or less △: Thickness ratio is greater than 1.07 and less than or equal to 1.1 ×: Thickness ratio is more than 1.1

[0075] 4-4. Flexibility of laminate Each laminate was bent 180° with a radius of curvature (300 μm), a load (50 mN, 1 minute) was applied from above, and then the laminate was returned to its original state. The presence or absence of cracks on the surface of the polymer layer was visually observed and evaluated according to the following criteria. [Evaluation Criteria] 〇: No cracks ×: Cracks have occurred

[0076] 4-5. Interlayer adhesion of laminates A rectangular test piece (100 mm long, 10 mm wide) was cut out from each laminate, and fixed at a position 50 mm from one end in the longitudinal direction of the test piece. The polymer layer and the copper foil were peeled off from one end in the longitudinal direction at an angle of 90° to the test piece at a pulling speed of 50 mm / min. The maximum load applied at that time was taken as the peel strength, and the interlayer adhesion was evaluated according to the following criteria. [Evaluation Criteria] ○: Peel strength is 15N / cm or more △: Peel strength is 10N / cm or more and less than 15N / cm ×: Peel strength is less than 10 N / cm

[0077] 4-6. Linear expansion coefficient of laminate The copper foil of each laminate was removed by etching with an aqueous solution of ferric chloride to prepare a single polymer layer. A square test piece measuring 180 mm square was cut from the prepared polymer layer, and the linear expansion coefficient of the test piece was measured in the range of 25°C to 260°C in accordance with the measurement method specified in JIS C 6471:1995, and evaluated according to the following criteria. [Evaluation criteria for linear expansion coefficient] ◯: The linear expansion coefficient is 75 ppm / ℃ or less. ×: The linear expansion coefficient is more than 75 ppm / °C.

[0078] 4-7.Dielectric tangent of laminate A rectangular test piece 100 mm long and 50 mm wide was cut out from each laminate, and the copper foil was removed by etching with an aqueous solution of ferric chloride to obtain a polymer layer alone. The dielectric loss tangent (measurement frequency: 10 GHz) of the polymer layer was measured using the SPDR (split post dielectric resonance) method and evaluated according to the following criteria. [Evaluation criteria for dielectric loss tangent] ○: Dielectric tangent is less than 0.0020 △: Dielectric tangent is 0.0020 or more and 0.0040 or less ×: Dielectric tangent is more than 0.0040 The results of the evaluations described in 4-1 to 4-6 are summarized in Table 2. The dielectric loss tangent of laminate 1 was measured at the same time as the measurement of the dielectric loss tangent in 4-6. and The relative dielectric constant of each of the three samples was 2.1 or less.

[0079] [Table 2] [Industrial Applicability]

[0080] The aqueous dispersion of the present invention has excellent dispersion stability and can be easily processed into films, fiber-reinforced films, prepregs, and metal laminates (metal foils coated with resin). The processed products obtained can be used as materials for antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, sliding bearings, etc.

Claims

1. An aqueous dispersion comprising particles of a tetrafluoroethylene-based polymer, inorganic particles having an average particle size of less than 10 μm, a polyhydric alcohol, and water, wherein the content of the inorganic particles is greater than the content of the tetrafluoroethylene-based polymer, and the content mass ratio of the polyhydric alcohol to water is 0.2 or more and 10 or less.

2. 2. The aqueous dispersion according to claim 1, wherein the tetrafluoroethylene polymer is a heat-fusible tetrafluoroethylene polymer having a carbonyl group-containing group or a hydroxyl group-containing group.

3. 3. The aqueous dispersion according to claim 1, wherein the particles of the tetrafluoroethylene-based polymer are particles of a heat-fusible tetrafluoroethylene-based polymer and particles of a non-heat-fusible tetrafluoroethylene-based polymer.

4. The aqueous dispersion according to any one of claims 1 to 3, wherein the inorganic particles are silica particles.

5. The aqueous dispersion according to any one of claims 1 to 4, wherein the inorganic particles have a scale-like or substantially spherical shape.

6. The aqueous dispersion according to any one of claims 1 to 5, which has a pH in the range of 5 to 10.

7. The aqueous dispersion according to any one of claims 1 to 6, wherein the polyhydric alcohol is an aliphatic polyhydric alcohol having a boiling point of 100°C or higher.

8. The aqueous dispersion according to any one of claims 1 to 7, further comprising an aromatic resin.

9. The aqueous dispersion according to claim 8 , wherein the aromatic resin is a precursor of a water-soluble aromatic polyamideimide or a precursor of a water-soluble aromatic polyimide.

10. 10. The aqueous dispersion according to claim 8, wherein the content of the aromatic resin is less than 10 mass% based on the mass of the tetrafluoroethylene-based polymer particles.

11. The aqueous dispersion according to any one of claims 1 to 10, further comprising a surfactant.

12. A method for producing a laminate, comprising applying the aqueous dispersion according to any one of claims 1 to 11 to a surface of a substrate, and heating the applied aqueous dispersion to form a polymer layer containing the tetrafluoroethylene-based polymer and the inorganic particles, and obtaining a laminate having the substrate and the polymer layer in this order.

13. The method according to claim 12, wherein the ten-point average roughness of the surface of the substrate is less than 0.1 μm.

14. The method according to claim 12 or 13, wherein the polymer layer has a thickness of 25 μm or more.

Citation Information

Patent Citations

  • Dispersion composition of fluorine containing meltable resin and coated product

    JP2001164064A

  • Aqueous dispersion type fluororesin coating composition

    WO2003011991A1

  • Polytetrafluoroethylene aqueous dispersion

    WO2021045228A1